Does high teacher autonomy support reduce smartphone use disorder in Chinese adolescents? A moderated mediation model. (June 2020) - Peng, Shun; Zhou, Bingping; Wang, Xia; Zhang, Hongpo; Hu, Xiangen
Highlights: Good teacher autonomy support (TAS) negatively predicted smartphone use disorder (SUD). Self-esteem mediated the relation between TAS and SUD. The impact of TAS on SUD was positive for those with lower life satisfaction. The impact of TAS on SUD was negative for those with higher life satisfaction. Abstract: The Interaction of Person-Affect-Cognition-Execution model (I-PACE; Brand, Young, Laier, Wölfling, & Potenza, 2016) proposes that addictive behavior is the result of the interaction of multiple factors. According to I-PACE model, perceived social support (teacher autonomy support), self-esteem, and gratification (life satisfaction) contribute to adolescent smartphone use disorder (SUD) (Brand et al., 2016). However, previous studies have rarely examined the interactive effects of teacher autonomy support, self-esteem and life satisfaction on adolescent SUD. The present study examined these relationships using a moderated mediation model in which self-esteem played a mediating role and life satisfaction played a moderating role in the relation between teacher autonomy support and adolescent SUD. A sample of 1912 Chinese adolescents completed measures of teacher autonomy support, self-esteem, life satisfaction, and adolescent SUD. Self-esteem mediated the association between teacher autonomy support and adolescent SUD. In addition, the relation between teacher autonomy support and SUD was moderated by life satisfaction: when the effect of life satisfaction was high, teacher autonomy support negatively predicted adolescent SUD, whereas when the effect of life satisfaction was low, teacher autonomy support was positively related to adolescent SUD. These findings advance our understanding of the effect of teacher autonomy support, self-esteem and life satisfaction on adolescent SUD. Limitations and implications of this study are discussed, such as teacher autonomy support may not reduce adolescent SUD, especially when their life satisfaction is low.